Peningkatan Keterampilan Sosial Anak Melalui Permainan Tradisional Ular-Ularan - Dwi Nurhayati Adhani; Inmas Toharoh Hidayah (Universitas Trunojoyo Madura, 2014)
In every child’s development always bring uniqueness that can not be suspected. According Hurluck growth and development of children include the development of emotional, physical, language and social. In this case to improve the social growth of children requires a skill. The research focus is to look at a design and implementation of traditional gemes on early childhood, as well as several important tradisional games in early childhood social development. This research type of field research, are qualitative. The results of this study stated that tradisional games can stimulate various aspects of child development in particular aspects of social skill. Through the games children can learn to socialize with friends, children learn compactness, children learn self-control or control their emotions, children learn to be responsible, children learn discipline with rules and learn to respect others. Thus the stimulation of traditional social skills through games and songs motion can make a child who has a personal emotional intelligence